Serous Cystadenocarcinoma Arising in Presumed Vitelline Duct Remnant: A Case Report and Implications in the Management of Cancer of Unknown Primary - Li Lei; Jeremy K. Deisch (Case Reports in Pathology)
Background. Malignant neoplasms arising in Meckel’s diverticulum, a vitelline duct remnant, are rare yet well-documented. Case Presentation. A 53-year-old previously healthy female presented with an enlarging midline abdominal wall mass. A computed tomography scan revealed a mass involving the linea alba, bilateral rectus abdominis, and subcutaneous fat. Extensive clinical workup failed to demonstrate other lesions, except local and paratracheal/hilar lymphadenopathy. Histopathologic examination of the resected tumor demonstrated a spectrum of serous neoplasia including serous cystadenoma, papillary serous carcinoma with numerous Psammoma bodies, and a poorly differentiated component. Immunophenotypically, the tumor cells were strongly positive for CK7, CK19, CA19.9, and MUC1 but negative for other lineage markers, findings suggestive of pancreatobiliary type differentiation. The patient died of the disease one year after the initial presentation despite chemotherapy, radiation, and surgery. Conclusion. We present a case of adenocarcinoma arising from the anterior midline abdominal wall, from presumed vitelline duct remnant, with histologic and immunophenotypic features of serous cystadenocarcinoma of pancreatobiliary origin. Though the origin from vitelline duct remnant is difficult to prove in this single case, understanding tumorigenesis of embryonic remnant origin is potentially important to improve the management of cancer of unknown primary.